2006
DOI: 10.1007/s11092-007-9033-8
|View full text |Cite
|
Sign up to set email alerts
|

Leadership as Accountability for Learning: The Effects of School Poverty, Teacher Experience, Previous Achievement, and Principal Preparation Programs on Student Achievement

Abstract: In the current era of accountability for achievement, school principals play the pivotal role of instructional leader. In a high-stakes testing environment, leadership preparation programs in universities and school districts need to be positively related to academic outcomes. The purpose of this study was to examine the relationship between school leadership preparation programs and student achievement in urban settings. Because leadership is contingent on the setting, school contextual factors and their impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 22 publications
3
27
0
Order By: Relevance
“…Teacher retention was shown to have significant positive impacts on student achievement (Barmby, 2006;Vanderhaar, Mu, & Rodosky, 2006). Vanderhaar et al (2006) found teachers' average years of teaching, along with student poverty level and previous testing achievement, were the best indicators of student achievement. To keep teachers in the field longer and increase their average years of experience, school officials should advocate practices that prevent teacher burnout.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Teacher retention was shown to have significant positive impacts on student achievement (Barmby, 2006;Vanderhaar, Mu, & Rodosky, 2006). Vanderhaar et al (2006) found teachers' average years of teaching, along with student poverty level and previous testing achievement, were the best indicators of student achievement. To keep teachers in the field longer and increase their average years of experience, school officials should advocate practices that prevent teacher burnout.…”
Section: Literature Reviewmentioning
confidence: 96%
“…(2003) found substantial relationships between school leadership and student achievement, citing previous revealing effect sizes as large as 0.50. Vanderhaar, Munoz, and Rodosky (2006) determined that principals playa pivotal role in transforming and shaping student achievement. Further research employing student achievement measures could illustrate the role that the psychological gender-leadership relationship plays in school success.…”
Section: Recommendationsmentioning
confidence: 99%
“…Moreover, a growing body of literature on the relationship between academic achievement and the concentration of poverty within a school has demonstrated that the effects of high concentrations of poverty often extend beyond the effects of an individual's poverty (Banks, 2001;Orfield & Lee, 2005;Vanderhaar, Muñoz, & Rodosky, 2006). Many studies operationalize collective SES using single variables, such as residing in social housing (Martens et al, 2014) or by simply asking principals what percentage of their students were of low SES, average SES, or high SES and then calculating a heterogeneity index similar to the Blau index of racial diversity or Simpson's index (1949) in ecological studies (Menzer & Torney-Purta, 2012) while others use a combination of multiple and varied factors.…”
Section: Conceptualizing Socioeconomic Statusmentioning
confidence: 99%
“…This trend suggests a possible limitation of the present study since intra-school tracking may further confound the results; however, it should be noted that the present study seeks to inform student school-assignment in districts with high geographic stratification of SES and cannot control for within-school tracking. Finally, covariates omitted to control for extraneous exogenous or endogenous effects, notably student priorachievement (e.g., Vanderhaar et al, 2006), run the risk of potential omitted variables bias, which can lead to overestimating the effects of peer SES. The present study takes into account prior student achievement by examining measures of student growth and controls for endogenous, school-level process variables while omitting school input variables which are highly correlated to the DI in an effort to mitigate the risk of multicollinearity.…”
Section: Peer Effects On Academic Achievementmentioning
confidence: 99%
See 1 more Smart Citation